Myocardial Performance Index as Related to Age in Normal Men With ideal Body Mass Index - Ali Jalil Malallah Al Rubaye; Saad Brais Mahdi Waeli; Kareem Jabur Mansur; Asaad Hasan Noaman (Zien Journals, 2022)
Tie index or what is called the myocardial performance index (MPI) is a ratio of isovolumic relaxation time and isovolumic contraction time to the ejection time. Global systolic and diastolic function is better estimated by this index, also it may be used as a sensitive marker for prediction a symptomatic heart failure and offering predictive information in various clinical situations. In the same context, increases in the age have been shown to exert an impact on the left ventricle (LV) preload and afterload and consequently LV function. Additionally Of note, studies regarding age specific cut-off points of MPI are limited and needs further assessment. Further, reports on interrelationship between MPI and different age groups are limited. This study is aimed to inspect the relationship between MPI and age. A total of 100 normal individuals were involved in this study. Each participant was subjected to thorough clinical and laboratory check up to exclude diseases that might affect the results. Four groups are divided on the bases of age: GROUP A: From 20 to 29year. GROUP B: from 30 to 39year, GROUP C: From 40 to 49 year, and GOUP D: From 50 to 60 year or more. Echocardiography was done for all participants with standard left lateral position. MPI was calculated as IVCT+IVRT/ET. In results, MPI was not changed significantly with age. Regarding individual components of Tei index, both ET and IVCT showed no relation with age, although the ET showed slight increase with increasing age, while IVRT was significantly different among age groups. In conclusion, myocardial performance index exhibited no relation with increasing age in normal men.
Keywords: Myocardial performance index; isovolumic contraction time; isovolumic relaxation time; ejection time.